2021
DOI: 10.1186/s40168-021-01144-4
|View full text |Cite
|
Sign up to set email alerts
|

Trophic level drives the host microbiome of soil invertebrates at a continental scale

Abstract: Background Increasing our knowledge of soil biodiversity is fundamental to forecast changes in ecosystem functions under global change scenarios. All multicellular organisms are now known to be holobionts, containing large assemblages of microbial species. Soil fauna is now known to have thousands of species living within them. However, we know very little about the identity and function of host microbiome in contrasting soil faunal groups, across different terrestrial biomes, or at a large spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 78 publications
0
18
0
Order By: Relevance
“…This is because microcosm experiments simplify the microbiome and resistome of soil animals, thus failing to reflect the risk of actual transmission of ARGs under field conditions. Several studies have confirmed that bacterial communities and ARGs are significantly correlated in various environments. ,, In addition, a recent study on the microbiome of soil food webs demonstrated that the diversity of animal bacterial community increases with increasing trophic levels . Therefore, we hypothesized that the variability of animal ARGs in soil food webs is related to their trophic levels.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…This is because microcosm experiments simplify the microbiome and resistome of soil animals, thus failing to reflect the risk of actual transmission of ARGs under field conditions. Several studies have confirmed that bacterial communities and ARGs are significantly correlated in various environments. ,, In addition, a recent study on the microbiome of soil food webs demonstrated that the diversity of animal bacterial community increases with increasing trophic levels . Therefore, we hypothesized that the variability of animal ARGs in soil food webs is related to their trophic levels.…”
Section: Introductionmentioning
confidence: 80%
“…For soil animal samples, enough soil was collected in the field and brought to the laboratory for animal separation. More details on the collection of soil and animal samples can be found in a previous literature …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial genera can specify the classification of bacteria relative to bacterial family level and indicate the function of bacteria in soil ecosystem, so we chose the bacterial genus level as the classification basis. Although there are inaccuracies to some extent in identifying bacterial genera or species, it is still acceptable to analyze the bacterial community at the genus level according to numerous studies. ,, OTUs with the sum representative sequences of all samples of <100 were discarded from the final OTU table. A phylogenetic tree was built by a Fast tree algorithm .…”
Section: Methodsmentioning
confidence: 99%
“…Soil contamination with antibiotics mainly occurs through sewage, , irrigation, , manure, , and sludge , application to fields resulting in, for example, high levels of oxytetracycline in Chinese soils . It is well-recognized that anthropogenic activities have increased both the diversity and abundance of resistomes in soils, with the potential for spread to humans through above- and below-ground pathways. Given the global nature of the problem, the World Health Organization has characterized resistomes as a global public health crisis…”
Section: Introductionmentioning
confidence: 99%